INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. SMGP ON COMMUNITY WELFARE AT PUNCAK SORIK MARAPI - Khoiriah, Midatul; Rahmat, Paisal; Affandi, Faisal; Nasution, Marlian Arif (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2024)
This research aims to determine the influence of Corporate Social Responsibility (CSR) of PT. SMGP towards Community Welfare in Puncak Sorik Marapi. The research method used was quantitative with random sampling techniques, the research sample was 98 respondents. Data analysis in this study uses a validity test with person correlation results for each question point > r table so that it can be stated that all points are valid, while the reliability test on variable X is 887 and variable Y is 735, the normality test is normally distributed because Asymp.sig (2-tailed) is 0.200 > 0.05, and the linearity test proves there is a linear relationship because the deviation from linearity value is > 0.05. Testing the hypothesis of this research using the t test obtained t-count10,191. This shows that there is an influence of Corporate Social Responsibility (CSR) on community welfare in Puncak Sorik Marapi District. and the coefficient of determination test results show 0.520, this provides an assumption that the influence of CSR on community welfare is 52.0% while the rest is influenced by other factors outside the research.